The high thermal conductive and flexible boron nitride/silicone rubber composites with segregated structure. (19th March 2021) - Ding, Jiwan; Zheng, Ruobing; Zhang, Yajie; Zhang, Xian; Liu, Gang; Zheng, Kang
Abstract: Silicone rubber (SR) composites filled with silicone rubber particles (SRP) and functionalized h-BN platelets were successfully prepared, which have high thermal conductivities and flexibility. The functionalization of h-BN adopts the combination of non-covalent and covalent modification. The Non-covalent functionalization of poly(dopamine) (PDA), which is deposited on the surface of h-BN platelets, improves the interfacial adhesion for grafting (3-aminopropyl) triethoxy-silan (KH550) by covalent modification (BN-PDA-KH550). To construct the thermal conductive pathway, silicone rubber particles are added. so that the fillers can distribute along the particle circumference by volume exclusion, which is advantageous for improving heat conduction of SR composites. The as-prepared 30 vol% BN-PDA-KH550@silicone rubber particles/silicone rubber composites (m-BN@SRP/SR) exhibited a relatively high thermal conductivity (2.24 W m −1 ·K −1 ), which is about 112 times of pure SR (0.20 W m −1 ·K −1 ). Besides, the m-BN@SRP/SR composites possessed satisfactory softness and excellent dielectric properties, which presented a broad application prospect in the field of electronic packaging.